The Clinical pilot study of Hwangryunhaedok-tang Pharmacopuncture therapy on Post-stroke depression - Juntae Je; Sangkwan Lee (Korean Pharmacopuncture Institute, 2010)
Objective : The purpose of this study is to determine the efficacy and safety of Hwangryunhaedoktang Pharmacopuncture (HHT-PA) therapy on post-stroke depression (PSD) in stroke patients. Methods : Fifteen PSD patients has been recruited and evaluated with liver function test (LFT) and renal function test (RFT) and depression scales, Beck Depression Inventory (BDI) and Hamilton Depression Rating Scale (HAM-D) before and after HHT-PA treatment. Results : HAM-D score significantly decreased after HHT-PA treatment regardless of improving of motor function. But BDI score did not decrease significantly. All results of LFT and RFT were in normal range before and after HHT-PA treatment. Conclusion : These results showed that HHT-PA decrease PSD symptoms and has safety on stroke patients, although has no effect on improving of motor impairment.